2012
DOI: 10.1007/s00520-012-1397-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life anticipated with different management strategies for febrile neutropenia in adult cancer patients

Abstract: Our study indicates that the majority of adult cancer patients would prefer an outpatient strategy for FN. However, patients' preferences vary substantially at the individual level. Implementation of outpatient strategies into routine clinical practice should consider this variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…In particular, 36% preferred an outpatient management with oral antibiotics, 21% an outpatient management with intravenous antibiotics, and 18% an oral treatment at home after an initial observation in the hospital [37]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 36% preferred an outpatient management with oral antibiotics, 21% an outpatient management with intravenous antibiotics, and 18% an oral treatment at home after an initial observation in the hospital [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Identification of patients suitable for outpatient management is crucial since this cost-effective strategy allows savings, limits the risk of hospital-acquired infections and improves the patients' quality of life [36,37]. FN patients with a MASCC score ≥ 21 and without other clinical warning signs can be safely managed in the outpatient setting if they are able to take oral medication and have a committed caregiver [38,39].…”
Section: Management Of Febrile Neutropeniamentioning
confidence: 99%
“…56 Of the remaining studies that considered acceptability in OPAT patients only, most involved multiple OPAT models (and did not differentiate between them in their findings), or did not specify the model(s) under study. In general, satisfaction with treatment was very high, 2,13,27,36,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] including when patients had to have frequent attendance at hospital. 5,84 Commonly perceived advantages of OPAT included the ability to resume daily activities, 2,27,71,73 feelings of improved self-esteem or greater freedom and control, 67,71,73,85,86 and not having to remain in or attend hospital.…”
Section: Patient Acceptabilitymentioning
confidence: 99%
“…5,12,13,15,25,27,36,41,67,68,70,73,[75][76][77][78][80][81][82]86,89 Only six interview-based studies were identified by the review. 35,37,79,85,88,99 The literature indicates that patients generally view OPAT very positively. The main benefits relate to the comfort of the home environment 56,85,86,99 and increased freedom and autonomy.…”
Section: Contextmentioning
confidence: 99%
“…Although most patients with a single axillary body temperature of ≥38˚C occurring between days 8 and 14 after the start of chemotherapy may have neutropenia and may be diagnosed with FN (10), outpatient management without initial assessment for these patients is routinely performed at our hospital. Implementation of this type of outpatient management can avoid unnecessary consultations, decrease costs, limit the risk of hospital-acquired infections and improve patients' quality of life (11)(12)(13), although it can also lead to insufficient initial assessment and inappropriate initial therapy. The JSMO guidelines do not recommend this type of outpatient management without initial assessment for febrile patients, although they also state that these recommendations may be modified, depending on the characteristics of individual malignancies and organs (5).…”
Section: Introductionmentioning
confidence: 99%